2x-1+4x=65

Simple and best practice solution for 2x-1+4x=65 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-1+4x=65 equation:



2x-1+4x=65
We move all terms to the left:
2x-1+4x-(65)=0
We add all the numbers together, and all the variables
6x-66=0
We move all terms containing x to the left, all other terms to the right
6x=66
x=66/6
x=11

See similar equations:

|         14(-3z+2)-10=-108 | | 7x-3=3x-63 | | 4/47x+16/47=12/47 | | 23-4c=15 | | 1/5(9)=x | | 37+2b=83 | | 14x-2=-6 | | 4x2-17x-42=0 | | 5n+35=2(1-7n) | | X-1.34=0.6x-1.7 | | 4x-88=6x | | -40=z/3-50 | | x+3.2=−3.5 | | 2(x+2)+2=-4-3(-8+4x) | | 5x+3x-6x=12 | | 20-x=128 | | 3.25y=26y= | | 7x2-6x-16=0 | | 4x+8=7.2 | | -8-5x+7x=8 | | 0.25+0.50+x=-0.75 | | b/5+1/8=11 | | d/3+10=13 | | 20x-15=15x+15 | | (7-4x=9) | | 49y^2+14y+1=0 | | 3x-3=18-5x+5 | | f/3+4=6 | | 9x+38=9x+38 | | 16-7x=-3x=2 | | 6(c)-5=37 | | (27/y^2)-y=0 |

Equations solver categories